Tracing women's romanticism : gender, history and transcendence - Lokke, Kari (Routledge studies in romanticism, 2004)
This volume argues that the künstlerromane of Mary Shelley, Bettine von Arnim, and George Sand offer feminist understandings of history and transcendence that constitute a critique of Romanticism from within.